Uczestnictwo strony pozwanej w procesie o stwierdzenie nieważności małżeństwa - Nowakowski, Bartosz (Ius Matrimoniale, 2013)
This publication discusses the significance of active participation of a respondent, their rights and obligations in the process for the declaration of the nullity of marriage. The author stresses a judge’s duty to do their best to, on the one hand, enable a respondent to participate in the process, and on the other hand, to make sure that a respondent does take part. It is therefore about the effectiveness of notifying about the process as well as the respondent ’s failure to appear, which cannot be accepted too easily, and the attempt to notify a party should not be a mere formality. Moreover, the author emphasises that respondent’s testimony are a important criterion helping to find the objective truth about a marriage. Finally, discusses the question of the inviolability of the right to defense and presenting respondent’s own arguments.